South African higher education language politics post #RhodesMustFall: The terrain of advanced language politics. Issue 1 (23rd March 2018) - Mwaniki, Munene
Abstract: In 2015, South African higher education witnessed student-driven activism in the form of various #movements, beginning with the #RhodesMustFall campaign at the University of Cape Town, which morphed into the national #FeesMustFall movement. A corollary to these #movements was a language-specific #movement namely #AfrikaansMustFall. Very little literature exists on this latter movement in contrast to the sizeable literature corpus on the other two #movements. While highlighting this hiatus in the research literature, through a combination of extensive literature review and polemical analytic auto-ethnographic analysis, the article argues that the language contestations in south African higher education after #RhodesMustFall transcend the provincialism that hitherto defined language politics in the sector. To advance this thesis, the article argues that south African higher education language politics post #RhodesMustFall are an invitation to the terrain of advanced language politics. Advanced language politics transcends the traditional (and somewhat normalised) realm of the analogous relationship between language, the nation(-state) and reductionist ethnocentrism, and ventures onto the realm of language as a marker and means to (re)affirm, celebrate and advance value in the furtherance of human dignity, (social) justice, diversity of peoples and knowledges, fluid and multiple identities, fraternity, equality, globalism and egalitarianism - including egalitarian knowledge access.